The relationship between the delivery of material by the instructor and the learning outcomes of bag knitting training participants at PKK Nagari Campago - Aisya, Siti Salma; Aini, Wirdatul (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2025)
This research was motivated by the low learning outcomes of bag knitting training participants, this was thought to be influenced by the delivery of material from the training instructor. The aim of this research activity is to find out: the delivery of material by the instructor, the learning outcomes of bag knitting training participants, and the relationship between the delivery of material by the instructor and the learning outcomes of bag knitting training participants at PKK Nagari Campago. The research was carried out using a quantitative approach with a correlational type. The research population was 25 participants who took part in bag knitting training activities. Meanwhile, the research sample was taken using a total sampling technique, namely 25 people. The research instrument for collecting data uses a questionnaire. Data analysis techniques use percentage and rank order formulas. The research results show that: (1) The delivery of material by the instructor is categorized as not optimal; (2) The learning outcomes of bag knitting training participants are categorized as low; and (3) There is a significant relationship between the delivery of material by the instructor and the learning outcomes of bag knitting training participants at PKK Nagari Campago. Research suggestions for bag knitting training instructors are to optimize the delivery of material by studying several methods in delivering material and for further researchers it is recommended to make a more in-depth theoretical study of this research, namely regarding the delivery of material by instructors with the learning outcomes of training participants.